Two-magnon scattering in the 5d all-in-all-out pyrochlore magnet Cd2Os2O7 - Thi Minh Hien Nguyen (Nature Portfolio, 2017)
Pyrochlore 5d transition metal oxides are expected to have interesting forms of magnetic order but are hard to study with conventional probes. Here the authors show that Raman scattering can be used to measure magnetic excitations in Cd2Os2O7 and that it exhibits complex spin-charge-lattice coupling.